2018
DOI: 10.1680/jgrma.17.00019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of submicron silica particles from rice husk

Abstract: Rice husk is considered an important silica source. In this work, microsilica particles were obtained by incineration of rice husk and milling of its ash. The synthesis process was carried out by incinerating the rice husk at 700°C, followed by acid leaching in order to remove inorganic impurities and finally mechanical ball milling at 0, 18, 36 and 72 h to reduce the particle size. Thermogravimetric analysis shows the thermal degradation of rice husk and elimination of organic components. The chemical composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The XRD pattern for RHBA and bench‐scale bio‐silica product from R A/F 6 g/g for a 1‐h extraction is shown in Figure 5. The RHBA peaks that appear on 2θ = 35°, 49°, and 58° indicate the presence of aluminum oxide, potassium oxide, and sodium oxide 1,41–46 . In addition, extracted bio‐silica from this study is amorphous and absent from the crystalline phase, which is expressed from the wide broad peak attributed at diffraction angle 22° 1,2,19,47 .…”
Section: Resultsmentioning
confidence: 69%
“…The XRD pattern for RHBA and bench‐scale bio‐silica product from R A/F 6 g/g for a 1‐h extraction is shown in Figure 5. The RHBA peaks that appear on 2θ = 35°, 49°, and 58° indicate the presence of aluminum oxide, potassium oxide, and sodium oxide 1,41–46 . In addition, extracted bio‐silica from this study is amorphous and absent from the crystalline phase, which is expressed from the wide broad peak attributed at diffraction angle 22° 1,2,19,47 .…”
Section: Resultsmentioning
confidence: 69%
“…These methods can optimize the pozzolanic properties as well as reduce the influence of the conditions of heat treatment on the husk. In this direction, several scientists studied the influences of RHA in the composition of a composite binder on hydration processes, microstructural features and the composition and microstructure of the ITZ between the cement matrix and aggregate [10,52]. During experimental studies, researchers revealed that the cement paste, including RHA, had a smaller quantity of calcium hydroxide because of the pozzolanic reaction [53].…”
Section: Pozzolanic Activitymentioning
confidence: 99%
“…Nevertheless, the sample S-3 presents the smallest particle size, with agglomerates and particles in nano-metric dimensions. If the material is subjected for longer to the collisions, intensive fracturing and welding generated in the milling process a reduction in the mean particle size could achieved [34]. Nanometric sizes were verified in the powder after 3 h milling time so that the mechanical ball milling showed to be effective for to obtain silica nanoparticles.…”
Section: Morphological Analysis By Scanning Electron Microscopymentioning
confidence: 96%
“…The ball milling method, in comparison with other methods, has many advantages such as effectiveness, high purity of products, moderate reaction temperature, controllability, ease, and reproducibility [33]. Nowadays, more work is required for the implementation of efficient methods; therefore, finding an inexpensive way to produce silica NPs from recycling sources great significance and addition to the efforts to protect the environment, since an alternative use is proposed for rice husks, which is a waste that requires adequate management to avoid contamination [34].…”
Section: Introductionmentioning
confidence: 99%